2013
DOI: 10.4103/2230-8598.123446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of needle stick injuries among nurses in a tertiary care hospital and their immediate response

Abstract: Prevalence of needle stick injuries among nurses in a tertiary care hospital and their immediate responseContext: Needle stick injuries (NSIs) are wounds caused by needles in health care setup that accidentally puncture the skin and may result in exposure to blood or other body fl uids. NSI is a major occupational health and safety issue faced by health care professionals globally. Nurses have the highest rate of needle stick injury among health care workers. Aims: To determine the prevalence of needle stick i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…33 In a study by Afridi et al in Pakistan, 41.9% of HCWs were injured while giving injections or drawing blood samples. 37 Injection was the most common cause of activity-related injuries in the findings of the studies of Laishram et al, 38 Quien et al, 39 Nsubuga et al, 40 and Kebede et al 32 Caution must be taken when comparing the current findings with those of the above-mentioned studies. This article is the analysis of 19 studies, while the other mentioned papers were based on one study.…”
Section: Discussionmentioning
confidence: 66%
“…33 In a study by Afridi et al in Pakistan, 41.9% of HCWs were injured while giving injections or drawing blood samples. 37 Injection was the most common cause of activity-related injuries in the findings of the studies of Laishram et al, 38 Quien et al, 39 Nsubuga et al, 40 and Kebede et al 32 Caution must be taken when comparing the current findings with those of the above-mentioned studies. This article is the analysis of 19 studies, while the other mentioned papers were based on one study.…”
Section: Discussionmentioning
confidence: 66%
“…12 Another study by Laishram J et al showed that most common cause of NSI among nursing staffs of NSI occurred by open bore needles (93%) during administration of IV and IM injections and drawing blood for laboratory tests. 13 In our study most of the healthcare staffs (97,88.8%) are vaccinated with hepatitis B vaccine. The hospital has a policy to evaluate every staffs vaccine status at the joining and arrange 1 st dose of vaccination among unvaccinated staffs on day of joining only.…”
Section: Discussionmentioning
confidence: 78%